Role of histopathology in the diagnosis of nail disorders. (August 2011) - Haldar, Shekhar; Khopkar, Uday
Nails have limited patterns of morphologic expression, hence it is often difficult for the clinician to reach a specific diagnosis based on clinical findings alone. A biopsy of the nail unit for histopathological examination offers the most dependable and definitive method in reaching an accurate diagnosis. In contrast to skin, the nail is not easy to biopsy and many physicians as well as patients are therefore reluctant to undertake this procedure. However, it can be performed safely, painlessly and with a minimum of scarring. The most common indication to perform a nail biopsy was to differentiate between nail psoriasis and onychomycosis. A well-timed biopsy can prevent serious outcomes in potentially harmful nail conditions (e.g., early detection of a subungual melanoma). At the same time, it can also rule out any worrisome nail condition in a clinically similar-appearing benign lesion, for example to rule out subungual melanoma in a patient presenting with melanonychia due to subungual hematoma. The primary aim of this article is to highlight the utility and importance of histopathology in diagnosing nail disorders.